Physicochemical determinants of distribution of sequence types (ST) of Burkholderia pseudomallei from small ruminant farms in Peninsular Malaysia - Sadiq Muhammad, Abubakar; Hassan, Latiffah; Abdul Aziz, Saleha; Zakaria, Zunita; Ismail Musa, Hassan; Mat Amin, Maswati (Researchers Links, 2023)
Physicochemical properties of the soil or water environment within which microorganisms dwell have been shown to influence the presence of Burkholderia pseudomallei. A total of 78 isolates, of which 56 are from soil and 22 from water obtained from livestock farm environments, were molecularly characterized by multilocus sequence typing (MLST) and analyzed against the environmental physicochemical properties from 33 livestock farms in four selected states of Negeri Sembilan, Pahang, Perak, and Selangor in Peninsular Malaysia. Multinomial logistic regression analysis found a significant association between soil water content and ST (sequence type) 84 (OR = 0.833, 95% CI: 0.708 to 0.980; p=0.027) when compared to ST51. This showed a unit increase in soil water contents was associated with a 1.2 times increase in the odds of recovering ST51 compared with the odds of recovering ST84. Also, a statistically significant protective association was recorded between water pH and ST84 (OR=0.401, 95% CI 0.195-0.828; p = 0.013) when compared to ST51. This showed that for a unit increase in water pH, there was a 2.5 times increase in the odds of recovering ST51 compared with the odds of recovering ST84. These findings suggested that variation in the occurrence of various B. pseudomallei STs is associated with variations in the environmental (soil and water) physicochemical factors. Physicochemical properties such as soil water content and water pH might have influenced the distribution of certain genotypes of B. pseudomallei in the endemic areas. This information could be useful for planning control programs tailored toward environmental interventions to reduce contamination in non-endemic areas.